Eksplorasi Media Album Berpuisi untuk Pembelajaran Menulis Puisi Siswa Kelas VIII di Kabupaten Cilacap - Ilawati Ilawati; Bhayu Anggita Subarkah; Mashudi Mashudi; Siti Faridah; Onok Yayang Pamungkas; Laily Nurlina (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study aims to evaluate the effectiveness of the Poetry Album as a learning medium for teaching poetry writing to eighth-grade students in Cilacap Regency, Indonesia. Utilizing a qualitative exploratory approach, the research was conducted in three public junior high schools, involving 192 students and three Indonesian language teachers. Data were collected through participatory observations, semi-structured interviews, and documentation of students' works, and were analyzed using Miles and Huberman's interactive analysis model. The results indicate that 96-98% of students enjoyed using this media, and the average scores of students' poetry ranged from 82 to 88. These findings suggest that the Poetry Album can enhance students' motivation, emotional engagement, and poetry writing skills. Furthermore, this media has proven effective in enriching the learning process aesthetically and creatively, in line with Rosenblatt's (1995) aesthetic response theory and Vygotsky's (1978) constructivist theory. Thus, the Poetry Album is relevant for aesthetic-based literary learning in secondary schools.